PEMBERDAYAAN WARGA BINAAN DALAM UPAYA PENCEGAHAN KEKERASAN DALAM RUMAH TANGGA - Nina Zainab; Indra Lorenly Nainggolan (Abdi Bhara, 2022)
The Understanding in the prevention of DomesticViolence can not only be done in the community in general, butalso for inmates/convicts who are serving sentences inCorrectional Institutions. Legal counseling in the form ofempowering inmates is intended so that when they are free andreunited with their families and communities, they can play asignificant role in preventing domestic violence. In counselingin the form of empowering inmates, the participants, in this casethe inmates/inmates who previously did not fully know aboutdomestic violence, understood it more and more so that it isexpected to be a provision in welcoming a new life when theyreunite with their families. This activity was carried out using anonline method via zoom where the participants, namelyinmates/prisoners were in the Pondok Bambu Rutan while thespeakers were lecturers from Bhayangkara University who wereon campus.